Fantastic Beasts: The Secrets of Dumbledore (DVD) - Miller, Ezra; Waterston, Katherine; Fogler, Dan; Coyle, Richard; Rowling, J. K.; Mikkelsen, Mads, 1965-; Law, Jude, 1972-; Redmayne, Eddie, 1982-; Sudol, Alison, 1984-; Turner, Callum, 1990- ([United States] : Warner Bros., 2022)
Professor Albus Dumbledore knows the powerful dark wizard Gellert Grindelwald is moving to seize control of the wizarding world. Unable to stop him alone, he entrusts Magizoologist Newt Scamander to lead an intrepid team of wizards, witches, and one brave Muggle baker on a dangerous mission, where they encounter old and new beasts and clash with Grindelwald's growing legion of followers. But with the stakes so high, how long can Dumbledore remain on the sidelines?
"No other film series works in such intricate, multiple-installment arcs, planting details that will almost certainly pay off in forthcoming chapters."--Variety
"There's a renewed emphasis on magical creatures and another decidedly political bent to the franchise as it digs into dark themes and offers a bewitching goofy side."--USA Today
"This entertaining Harry Potter prequel buries memories of the Grindelwald disaster."--Richard Roeper
06/28/2022
new dvd 2022 summer.
Director, David Yates.
Mads Mikkelsen, Jude Law, Ezra Miller, Eddie Redmayne, Katherine Waterston, Alison Sudol, Dan Fogler, Callum Turner, Richard Coyle.
MPAA rating: PG-13.
DVD.
Keywords: Action and adventure; Fantasy; Drama; Action and adventure films; Based on the book